2014
DOI: 10.1002/aur.1401
|View full text |Cite
|
Sign up to set email alerts
|

Time Reproduction Performance Is Associated With Age and Working Memory in High‐Functioning Youth With Autism Spectrum Disorder

Abstract: Lay Abstract Temporal processing refers to our ability to “sense” or register the passage of time and to use that information to guide behavior. There is evidence that children with autism spectrum disorders (ASD) differ from children without ASD in their ability to process temporal information. Prior research has shown that age and working memory (the ability to hold and manipulate information in short-term memory storage) impact performance on temporal processing tasks in typically developing children, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
13
0
5
Order By: Relevance
“…Handwriting challenges might be one explanation for these difficulties as they may compromise the cognitive resources needed for writing in general including writing conventions (Hellinckx et al 2013). In addition, deficits in working memory may make it challenging to consider and operationalize all aspects of the writing process simultaneously (Brenner et al 2015). Finally, language deficits may impact not only pragmatics, but may have a more significant influence in terms of the production and understanding of grammatically correct content (Dockrell et al 2014).…”
Section: Strategies To Support Writing Conventionsmentioning
confidence: 99%
“…Handwriting challenges might be one explanation for these difficulties as they may compromise the cognitive resources needed for writing in general including writing conventions (Hellinckx et al 2013). In addition, deficits in working memory may make it challenging to consider and operationalize all aspects of the writing process simultaneously (Brenner et al 2015). Finally, language deficits may impact not only pragmatics, but may have a more significant influence in terms of the production and understanding of grammatically correct content (Dockrell et al 2014).…”
Section: Strategies To Support Writing Conventionsmentioning
confidence: 99%
“…Competent planning is crucial to decision making and involves inter‐temporal bridging/temporal foresight; the ability to make future choices based on previous experience and to understand the future consequences of one's actions. There is evidence that people with ASD have difficulty in planning [Bramham et al, ; Geurts et al, ; Ozonoff et al, ; Sinzig et al, ], reward related decision making [Minassian et al, ], temporal processing [Brenner et al, ; Szelag et al, ] and temporal discounting [Chantiluke et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Maister and Plaisted-Grant19 showed that while children aged 8 to 13 years were less accurate and more variable than age- and ability-matched typical children in the reproduction of short (<2 sec) and long (>45 sec) stimuli presented in the visual modality, no difficulties were found in reproducing durations 4–30 sec. Difficulties with temporal interval reproduction in autism have also been reported in children/adolescents20 and adults21, however other studies22 have found no such difficulties. Furthermore, with regards to temporal resolution, some studies2324 found reduced resolution in children and adolescents with autism, while others2225 found no such difficulties.…”
mentioning
confidence: 96%